Analytical Study of Teacher Educators’ Metaphors of Teaching (Journal of Education and Educational Development, 2020)
Teaching metaphor is an important phenomenon which can be used to determine teachers’ perceptions regarding their job and their workplace (Turunen, 2003). This study was aimed to explore the metaphors of junior and senior teacher educators to get insights of what teaching was for them. A comparative analysis between the junior and senior teacher educators helped to understand how these metaphors changed over time. Data for the qualitative study were collected from the districts of Sargodha, Khushab and Mianwali situated in the province of Punjab, Pakistan. Fifty teacher educators teaching at postgraduate level participated in the study and filled in the survey questionnaire. The data were coded and analysed qualitatively. Six themes emerged from the data: religious obligations, economic activities, nature compatibility, life processes, emotional affiliations, and thought provoking activities.These themes were compatible with Chen’s (2013) classification of teachers’ personal metaphors. The implications of metaphors could be used to enhance critical thinking of teacher educators to improve the quality of education